Distribution of Major Pilin Subunit Genes Among Atypical Enteropathogenic Escherichia coli and Influence of Growth Media on Expression of the ecp Operon - Munhoz, Danielle D.; Nara, Júlia M.; Freitas, Natália C.; Moraes, Claudia T. P.; Nunes, Kamila O.; Yamamoto, Bruno B.; Vasconcellos, Francielli M.; Martínez-Laguna, Ygnacio; Girón, Jorge A.; Martins, Fernando H.; Abe, Cecilia M.; Elias, Waldir P.; et al. (Frontiers in Microbiology, 2018)
Atypical enteropathogenic Escherichia coli (aEPEC) strains are unable to produce the bundle-forming pilus (BFP), which is responsible for the localized adherence pattern, a characteristic of the pathogenicity of typical EPEC strains. The lack of BFP in aEPEC strains suggests that other fimbrial or non-fimbrial adhesins are involved in their adhesion to the host cells. The aim of this study was to investigate the distribution of major subunit fimbrial genes known to be important adherence factors produced by several E. coli pathotypes in a collection of 72 aEPEC strains. Our results demonstrate that a high percentage (94-100%) of aEPEC strains harbored ecpA, fimA, hcpA, and lpfA fimbrial genes. Other fimbrial genes including pilS, pilV, sfpA, daaC, papA, and sfa were detected at lower frequencies (1-8%). Genes encoding fimbrial subunits, which are characteristic of enteroaggregative E. coli or enterotoxigenic E. coli were not found. No correlation was found between fimbrial gene profiles and adherence phenotypes. Since all aEPEC strains contained ecpA, the major pilin gene of the E. coli common pilus (ECP), a subset of ecpA+ strains was analyzed for transcription of ecpRABCDE and production of ECP upon growth in three different culture conditions at 37oC. Transcription of ecpRABCDE occurred in all conditions; however; ECP production was medium dependent. In all, the data suggest that aEPEC strains are highly heterogeneous in terms of their fimbrial gene profiles. Despite lacking BFP production, other mechanisms of cell adherence exist in aEPEC strains to ensure host colonization, e.g. mediated by other prevalent pili such as ECP. Moreover, the production of ECP by aEPEC strains might be influenced by yet unknown post-transcriptional factors.